Bioactive ent-kaurane diterpenoids from Isodon rubescens. (November 2017) - Zhang, Yuan-Yuan; Jiang, Hua-Yi; Liu, Miao; Hu, Kun; Wang, Wei-Guang; Du, Xue; Li, Xiao-Nian; Pu, Jian-Xin; Sun, Han-Dong
Abstract: Seven previously undescribed 7, 20-epoxy- ent -kaurane diterpenoids, isojiangrubesins A–G, along with seventeen known ones, were isolated from the aerial parts of Isodon rubescens . Their structures were characterized on the basis of spectroscopic methods and signal-crystal X-ray diffraction. All of these compounds were evaluated for their in vitro cytotoxicity against five human tumor cell lines (HL-60, SMMC-7721, A-549, MCF-7, and SW480). Four isolates exhibited significant inhibitory ability against all cell lines, with IC50 values ranging from 0.5 to 6.5  μ M; They also strongly inhibited NO production in LPS-stimulated RAW264.7 cells. Graphical abstract: Seven previously undescribed ent -kaurane diterpenoids and seventeen known ones were isolated from the aerial parts of Isodon rubescens, four of which exhibited significant in vitro cytotoxicity (IC50 0.5–6.5  μ M) and NO production inhibitory activities (IC50 0.8–1.3  μ M).Image 1 Highlights: Seven previously undescribed ent -kaurane diterpenoids were isolated from Isodon rubescens . The absolute configurations of isojiangrubesins A and D were determined by X-ray diffraction. All compounds were evaluated for their in vitro cytotoxicity. Several compounds were tested for their NO production inhibitory activities.